Prenatal Ultrasonic Diagnosis of Persistent Right Umbilical Vein with Single Umbilical Artery in Twin Pregnancy: A Case Report - Shubhi Gaur; Pratap Singh Parihar; Vaishali Dhawan; Devyansh Nimodia; Prasad Sanjay Desale (Journal of Clinical and Diagnostic Research)
Persistent Right Umbilical Vein (PRUV) is a developmental abnormality of the vascular system that occurs during embryonic development when the right umbilical vein remains open while the left umbilical vein becomes atretic. PRUV presents in two forms: the extrahepatic variety, which is less prevalent but more often associated with complications, and the intrahepatic type, which is the most common (90-95%). A Single Umbilical Artery (SUA) occurs when there is only one umbilical artery in the cord, and it is associated with an increased risk of various abnormalities, including cardiovascular defects. Hereby, the authors present a case report of a 32-year-old primigravida, approximately 20.3 weeks into her pregnancy, underwent an anomaly scan that revealed a two-vessel umbilical cord, showing an SUA and a PRUV in one of the foetuses, while both foetuses demonstrated normal intrauterine growth. PRUV in foetuses is linked to preterm births, oligohydramnios, and intrauterine growth restriction. It can also lead to gastrointestinal malformations, various cardiac anomalies, skeletal malformations, urinary tract anomalies, and SUA defects. Therefore, prenatal diagnosis of PRUV is essential.